The Global Integrated Pest Management Facility - Kelly, Lauren (World Bank, Washington, DC, 2014)
At the request of the World Bank's Executive Board, the Bank's Operations Evaluation Department (OED) has been conducting an evaluation of the Bank's involvement in global programs. The Phase 1 Report titled The World Bank's Approach to Global Programs focused on the strategic and programmatic management of the Bank's global portfolio of 70 programs in five Bank Networks (a cluster of closely related sectors) and was presented to the Committee on Development Effectiveness (CODE) on June 12, 2002. This case study is one of 26 and derives additional lessons for the Bank's strategic and programmatic management of global programs as well as lessons for the design and management of individual programs. This case study assesses the value added by the Bank's participation in the Global IPM Facility with a view to learning lessons for the Bank s future involvement in global programs. This is not a programmatic evaluation of the Global IPM Facility, nor a substitute for a thorough external independent evaluation. Several studies using new survey data detailing the substantial health and ecological benefits of IPM have emerged that contend that IPM does not result in a loss in production. Yet the debate continues about the most cost-effective and fiscally sustainable approach to extending knowledge about IPM practices to farmers.